APLIKASI METODE PUNCAK AMBANG BATAS MENGGUNAKAN PENDEKATAN DISTRIBUSI PARETO TERAMPAT DAN ESTIMASI PARAMETER MOMEN-L PADA DATA CURAH HUJAN (Studi Kasus : Data Curah Hujan Kota Semarang Tahun 2004-2013) - Tyas Estiningrum; Agus Rusgiyono; Yuciana Wilandari (Jurnal Gaussian, 2015)
The rainfall with very high intensity cause a lot of problem like flood, landslide and be a factor restricting of flight aircraft at the airport. One of the methods that can be use to analyze such extreme events is Peak Over Threshold (POT) with distribution approach Generalized Pareto Distribution (GPD) include in the Extreme Value Theory (EVT). L-Moment method used for estimation of scale and shape parameter from GPD. In this research, data used is daily rainfall data of the Semarang city in 2004-2013 that recorded at the Meteorological Station of Class II Ahmad Yani Semarang. Daily rainfall data is analyzed each year during the rainy season. Result of analysis of the data shows rainfall there are heavy tail that indicates there is a possibility of occurrence extreme value. Return level obtained indicated occurrence of precipitation with very high intensity for the period of rainy season in 2006/2007, 2009/2010, 2010/2011, 2011/2012, 2012/2013 and 2013/2014 with intensity of rainfall 117,1905730 mm/day, 118,6389421 mm/day, 106,5032441 mm/day, 107,2133094 mm/day, 108,2262353 mm/day dan 111,2356887 mm/day.Keyword : Rainfall, Peak Over Threshold, Generalized Pareto Distribution, Extreme Value Theory, L-Moment, Return level.